PENINGKATAN KETERAMPILAM MENULIS SISWA SMA MELALUI PROGRAM PELATIHAN PENULISAN KARYA TULIS ILMIAH [IMPROVING HIGH SCHOOL STUDENT’S WRITING SKILLS THROUGH A SCIENTIFIC WRITING TRAINING PROGRAM] - Niko Sudibjo; Rudy Pramono; HG Retno Harsanti (Universitas Pelita Harapan, 2018)
Writing scientific papers is an important skill for all students in undergoing their education at schools and continuing their studies at universities. The skills to write scientific works are needed by the students in delivering their ideas scientifically and responsibly. Unfortunately, there are not many schools that equip their students to understand the importance of scientific writing skills and how to implement them properly so that the students experience difficulties in carrying out various tasks in writing scientific papers, both at the school levels and in the next stages of their higher education. The purpose of the scientific writing training conducted in the study was to provide an understanding of the importance of having scientific writing skills and helping Dian Harapan Daan Mogot high school students to have basic skills in writing scientific papers. This activity included an explanation of the materials of writing scientific papers and a training on writing scientific papers. The data were collected using the tests and questionnaires given to 58 students. The data obtained were analyzed descriptively and the mean comparisons were tested through the Wilcoxon test. The results of this activity have indicated that the training provided can improve the students' scientific writing skills significantly.